Interleukin-1β Enhances Umbilical Cord Mesenchymal Stem Cell Adhesion Ability on Human Umbilical Vein Endothelial Cells via LFA-1/ICAM-1 Interaction - Tsai-Yi Wu; Ya-Han Liang; Jiahn-Chun Wu; Hwai-Shi Wang (Hindawi Limited, 2019)
The migration of administered mesenchymal stem cells (MSCs) to sites of injury via the bloodstream has been demonstrated. However, the underlying mechanisms of umbilical cord MSC adhesion to endothelial cells during transendothelial migration are still unclear. In this study, our data showed that IL-1β induced LFA-1 expression on MSCs and ICAM-1 expression on HUVECs. We then pretreated MSCs with protein synthesis inhibitor cycloheximide. The results showed that IL-1β induced LFA-1 expression on the surface of MSCs via the protein synthesis pathway. Through the p38 MAPK signaling pathway inhibitor SB 203580, we found that IL-1β induces the expression of LFA-1 through p38 MAPK signaling and enhances ICAM-1 expression in HUVECs. In addition, IL-1β-induced MSC adhesion to HUVECs was found to be inhibited by IL-1RA and the LFA-1 inhibitor lovastatin. These results indicate that IL-1β promotes the cell adhesion of MSCs to HUVECs through LFA-1/ICAM-1 interaction. We address the evidence that the cell adhesion mechanism of IL-1β promotes MSC adhesion to HUVECs. The implications of these findings could enhance the therapeutic potential of MSCs.